Trauma at home: The importance of listening - Basir Ah Azizi (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas, 2018)
This short case history describes the counselling process with an adolescent girl in Afghanistan. It illustrates the lack of sexual education for children and adolescents in Afghan society and reaffirms that listening is the most important part of counselling. Listening includes showing that you believe the client, being careful with questions and giving the client the feeling that she does not have to justify herself.